Climate Adaptive Silviculture for the City: Practitioners and Researchers Co-create a Framework for Studying Urban Oak-Dominated Mixed Hardwood Forests - Piana, Max R.; Hallett, Richard A.; Johnson, Michelle L.; Sonti, Nancy F.; Brandt, Leslie A.; Aronson, Myla F. J.; Ashton, Mark; Blaustein, Max; Bloniarz, David; Bowers, Ashley A.; Carr, Megan E.; D’Amico, Vince; et al. (Frontiers in Ecology and Evolution, 2021)
Urban forested natural areas are an important component of the forest and tree canopy in northeastern urban areas. Although similar to native forests in surrounding regions in structure, composition, and function, these natural areas are threatened by multiple, co-occurring biological and climate stressors that are exacerbated by the urban environment. Furthermore, forests in cities often lack application of formal silvicultural approaches reliant upon evidence-based applied ecological sciences. These include both urban- and climate-adapted silvicultural techniques to increase the resilience and sustainability of native forests in cities. With this in mind, we convened a group of urban forest practitioners and researchers from along a latitudinal gradient in the northeastern U.S. to participate in a workshop focused on co-developing long-term, replicated ecological studies that will underlie the basis for potential silvicultural applications to urban forests. In this article we review the process and outcomes of the workshop and identify similarities and differences in management goals, forest vulnerability, and adaptive capacity across the region. We discuss the social and ecological challenges of managing urban oak-dominated mixed hardwood forests relative to non-urban forests and identify potential examples of urban- and climate-adapted silviculture strategies created by practitioners and researchers. In doing so, we highlight the challenges and need for basic and long-term applied ecological research relevant to silvicultural applications in cities.